2017
DOI: 10.1002/ejic.201701049
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide as Feedstock in Selective Oxidation of Propane

Abstract: Carbon dioxide is a promising nonconventional oxidant for catalytic dehydrogenation of lower alkanes to olefins. The lower catalytic activity of CO 2 compared to oxygen, which is typically used in oxidative dehydrogenation (ODH), also means that more reactive olefins are less likely to undergo undesirable combustion in the presence of CO 2 . Supported vanadia catalysts were synthesized by incipient wetness impreg- [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Na-promoted SiO 2 supports have also been employed in an attempt to anchor more monovanadate species with the surface Si−O−Na + . 120 Characterization results confirm the improved surface V density, but along with the formation of inactive Na metavanadate species that selectively produce CO instead of C 3 H 6 (Table 4).…”
Section: Oxidative Dehydrogenation Of Propane With Carbon Dioxidementioning
confidence: 57%
See 1 more Smart Citation
“…Na-promoted SiO 2 supports have also been employed in an attempt to anchor more monovanadate species with the surface Si−O−Na + . 120 Characterization results confirm the improved surface V density, but along with the formation of inactive Na metavanadate species that selectively produce CO instead of C 3 H 6 (Table 4).…”
Section: Oxidative Dehydrogenation Of Propane With Carbon Dioxidementioning
confidence: 57%
“…To alleviate CO 2 poisoning, a relatively higher but proper CO 2 partial pressure is necessary to ensure more oxidized metal species for the ODHP reaction. Na-promoted SiO 2 supports have also been employed in an attempt to anchor more monovanadate species with the surface Si–O–Na + . Characterization results confirm the improved surface V density, but along with the formation of inactive Na metavanadate species that selectively produce CO instead of C 3 H 6 (Table ).…”
Section: Oxidative Dehydrogenation Of Propane With Carbon Dioxidementioning
confidence: 89%
“…[8][9][10][11][12][13] Although reaction with CO2 generally leads to lower conversion in comparison to commercialized dehydrogenation processes, the selectivity in a CO2-ODH reaction is significantly improved. 14,15 The mechanism for the ODH of light alkanes with CO2 has not been thoroughly explained, although different pathways have been proposed. It has been reported that the redox and acidbase properties of oxides can determine which of two pathways the reaction takes.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, vanadium oxide can form vanadate with alkali metals. Guliants et al varied the surface coverage of VO x species by using sodium on the silica surface [86]. They found that Na ?…”
Section: Vanadium-based Catalystsmentioning
confidence: 99%